The Association Between Operating Room Personnel and Turnover With Surgical Site Infection in More Than 12 000 Neurosurgical Cases. Issue 6 (December 2016) - Wathen, Connor; Kshettry, Varun R.; Krishnaney, Ajit; Gordon, Steven M.; Fraser, Thomas; Benzel, Edward C.; Modic, Michael T.; Butler, Sam; Machado, Andre G.
Abstract : BACKGROUND: Surgical site infection (SSI) contributes significantly to postoperative morbidity and mortality and greatly increases the cost of care. OBJECTIVE: To identify the impact of workflow and personnel-related risk factors contributing to the incidence of SSIs in a large sample of neurological surgeries. METHODS: Data were obtained using an enterprisewide electronic health record system, operating room, and anesthesia records for neurological procedures conducted between January 1, 2009, and November 30, 2012. SSI data were obtained from prospective surveillance by infection preventionists using Centers for Disease Control and Prevention definitions. A multivariate model was constructed and refined using backward elimination logistic regression methods. RESULTS: The analysis included 12 528 procedures. Most cases were elective (94.5%), and the average procedure length was 4.8 hours. The average number of people present in the operating room at any time during the procedure was 10.0. The overall infection rate was 2.3%. Patient body mass index (odds ratio, 1.03; 95% confidence interval [CI], 1.01-1.04) and sex (odds ratio, 1.36; 95% CI, 1.07-1.72) as well as procedure length (odds ratio, 1.19 per additional hour; 95% CI, 1.15-1.23) and nursing staff turnovers (odds ratio, 1.095 per additional turnover; 95% CI, 1.02-1.21) were significantly correlated with the risk of SSI. CONCLUSION: This study found that patient body mass index and male sex were associated with an increased risk of SSI. Operating room personnel turnover, a modifiable, work flow–related factor, was an independent variable positively correlated with SSI. This study suggests that efforts to reduce operating room turnover may be effective in preventing SSI. ABBREVIATIONS: OR, operating room SSI, surgical site infection